2021
DOI: 10.21037/tcr-20-2269
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CEA and CA19-9 in patients with local advanced rectal cancer receiving neoadjuvant chemoradiotherapy, radical surgery and postoperative chemotherapy

Abstract: Background: We aim to investigate the prognostic factors and evaluate the role of carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) in local advanced rectal cancer (LARC) patients who received neoadjuvant chemoradiotherapy (neo-CRT), radical surgery and postoperative chemotherapy.Methods: In total, 197 cases of LARC patients who underwent neo-CRT, total mesorectal excision (TME), and adjuvant chemotherapy were recruited. Serum levels of CEA and CA19-9 were detected both at baseline and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…CEA is a superfamily of glycoproteins present on cell membranes and has been shown to be participated in the metastasis and recurrence of colorectal cancer due to an essential role in cell recognition and adhesion [23,24]. Similar to previous studies [17], the elevated CEA level contributed to the clinical application of model 1 in our study, which might indicate that the CEA level is a necessary test for preoperative and postoperative review [25]. Based on T2WI, LNs with short-axis diameter of less than 5 mm and three malignant morphologic criteria (including spiculated border, round shape and heterogenous signal intensity) or short diameter between 5 and 9 mm and two malignant criteria or greater than 9 mm were considered as suspicious metastatic LNs [18,26,27].…”
Section: Discussionsupporting
confidence: 88%
“…CEA is a superfamily of glycoproteins present on cell membranes and has been shown to be participated in the metastasis and recurrence of colorectal cancer due to an essential role in cell recognition and adhesion [23,24]. Similar to previous studies [17], the elevated CEA level contributed to the clinical application of model 1 in our study, which might indicate that the CEA level is a necessary test for preoperative and postoperative review [25]. Based on T2WI, LNs with short-axis diameter of less than 5 mm and three malignant morphologic criteria (including spiculated border, round shape and heterogenous signal intensity) or short diameter between 5 and 9 mm and two malignant criteria or greater than 9 mm were considered as suspicious metastatic LNs [18,26,27].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have confirmed that many clinical indicators of patients with malignant tumors can be affected by chemotherapeutic drugs ( 8 , 9 ), and these indicators can also be used to predict the efficacy of neoadjuvant chemotherapy. Carcinoembryonic antigen (CEA) is a common biological indicator for CRC patients ( 10 , 11 ), but a study showed that CEA level at baseline was not significantly related to the progression-free survival (PFS) rate of CRC patients with liver metastasis who received neoadjuvant treatment ( 12 ). Therefore, it is of great significance to find new biological indicators to predict the efficacy of neoadjuvant chemotherapy in CRC patients.…”
Section: Introductionmentioning
confidence: 99%